Accuracy-aware data collection in wireless sensor networks. (2018) - Bi, Ran; Zheng, Xu; Tan, Guozhen
Data collection is a fundamental task in wireless sensor networks (WSNs). For a given filter, the sensor node sends the update to the base station if the sensed data is beyond the range of the filter. In this paper, we investigate the accuracy-aware approach for approximate data collection. The filter assignment for optimising the average of valid filter time is formalised as an integer optimisation problem and the hardness of this problem is proven to be NP-Complete. A greedy heuristic based algorithm with low computation overhead is proposed. To balance the valid filter time, the filter assignment for optimising the minimum valid time is formalised as a general max-min problem. We analyse the hardness of the problem and propose an approximation algorithm. The experimental results show that our algorithms achieve better results in terms of communication cost and expected time of valid filters.